Brain haemosiderin in older people: pathological evidence for an ischaemic origin of magnetic resonance imaging (MRI) microbleeds. Issue 3 (April 2014) - Janaway, B. M.; Simpson, J. E.; Hoggard, N.; Highley, J. R.; Forster, G.; Drew, D.; Gebril, O. H.; Matthews, F. E.; Brayne, C.; Wharton, S. B.; Ince, P. G.; ,
<x xml:space="preserve">Abstract</x> Introduction Magnetic resonance imaging (MRI) cerebral microbleeds (CMB) arise from ferromagnetic haemosiderin iron assumed to derive from extravasation of erythrocytes. Light microscopy of ageing brain frequently reveals foci of haemosiderin from single crystalloids to larger, predominantly perivascular, aggregates. The pathological and radiological relationship between these findings is not resolved. Methods Haemosiderin deposition and vascular pathology in the putamen were quantified in 200 brains donated to the population‐representative Medical Research Council Cognitive Function and Ageing Study. Molecular markers of gliosis and tissue integrity were assessed by immunohistochemistry in brains with highest (n = 20) and lowest (n = 20) levels of putamen haemosiderin. The association between haemosiderin counts and degenerative and vascular brain pathology, clinical data, and the haemochromatosis (HFE) gene H63D genotype were analysed. The frequency of MRI CMB in 10 cases with highest and lowest burden of putamen haemosiderin, was compared using post mortem 3T MRI. Results Greater putamen haemosiderin was significantly associated with putaminal indices of small vessel ischaemia (microinfarcts, P < 0.05; arteriolosclerosis, P < 0.05; perivascular attenuation, P < 0.001) and with lacunes in any brain region (P < 0.023) but not large vessel disease, or whole brain measures of neurodegenerative pathology. Higher levels of putamen haemosiderin correlated with more CMB (P < 0.003). Conclusions The MRI‐CMB concept should take account of brain iron homeostasis, and small vessel ischaemic change in later life, rather than only as a marker for minor episodes of cerebrovascular extravasation. These data are of clinical relevance, suggesting that basal ganglia MRI microbleeds may be a surrogate for ischaemic small vessel disease rather than exclusively a haemorrhagic diathesis.